DEVELOPING A DIVERSIFIED EVALUATION SYSTEM OF STUDENT DEVELOPMENT: INNOVATION FROM EDUCATION INFORMATISATION IN CHINA - Kun Ma,; Kenny Chean Soon Lee,; Seng yue Wong,; Xiaoli Pan,; Tiantian Qi,; Yunyun Wang, (Fonseca, Journal of Communication, 2024)
With the assistance of big data technology, diversified evaluation methods are used as a baton to promote students’ comprehensive development. Based on this, a new educational program for the new era faces challenges such as single evaluation dimensions, single evaluation subject, single evaluation approach, complex quantification and challenging collection of process data. Therefore, it is imperative to promote the reform of the evaluation system. Based on the diversified evaluation of the educational background, this paper adopts the research and case study methods and combines qualitative and quantitative methods. Students, teachers, families, and schools are taken as evaluation subjects. Students’ moral, intellectual, physical, aesthetic, and labour development process data are collected, shared, and analysed. Finally, referring to practical cases, a complete data chain and theoretical analysis basis is formed, effectively supporting diversified evaluation, promoting the integration of five aspects of education and generating evaluation reports and development predictions.